Peningkatan Hasil Belajar Peserta Didik Melalui Pembelajaran Berbasis Masalah Dan Pemanfaatan Android Pada Mata Pelajaran PaAI BP Di SMKN 1 Batipuh - Andri Yani, Nicha (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
improve student learning outcomes through the implementation of the [mention the method, e.g., cooperative learning] approach. The research method employed is classroom action research (CAR) consisting of two cycles, each including planning, implementation, observation, and reflection stages. The results indicate that this approach significantly enhanced student learning outcomes from Cycle I to Cycle II. Furthermore, student engagement in the learning process increased, encompassing cognitive, affective, and psychomotor aspects. These findings align with constructivist theory, which emphasizes the importance of active student involvement in learning. Therefore, this approach is effective in enhancing the quality of education.